PERMASALAHAN DALAM IMPLEMENTASI KONSEP PENGEMBANGAN PERIKANAN TERPADU - Budy Wiryawan; Sugeng H. Wisudo; Mulyono S. Baskoro (Buletin PSP, 2008)
Economic pressure become very dominant influences behavior of coastal community in exploiting fishery resources. Sustainability of fishery resources utilization often less attention in fulfilling demand of global market following with increasingly of human population. This problems will generate degradation of marine ecosystem with increasing magnitude and scale. To overcome those problems, an important approach is by increasing public awareness in management of fishery resources. . Fishery development concept is actually focusing on increasing prosperity by increasing employment opportunity and ensuring resources sustainability.By increasing fish consumption and domestic income will generate fishery sector development, however resources and environmental sustainability, will be the main priorit. Recommendation could be suggested, i,e : fisheries management and regulation, collaboration and institutional development and increasing of applied fishery science and technology.